2010
DOI: 10.1007/s12170-010-0117-5
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes in the Elderly

Abstract: Older adults with diabetes constitute a rapidly increasing population in the United States. Cardiovascular diseases occur at higher frequency in this population. Until recently, optimal goals of glycemic control as well as risk factor management (hypertension and lipids) to prevent cardiovascular morbidity and mortality in older adults with diabetes were unclear. Several clinical trials in recent years have shown minimal benefits and in certain populations (e.g. with high co-morbidities), increased risk for po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…in 1985. Ever since its discovery, many people have investigated it because of its unique physical and chemical properties . Researchers have found that C 60 has a tremendous capacity to react with radicals to yield corresponding radical adducts.…”
Section: Introductionmentioning
confidence: 99%
“…in 1985. Ever since its discovery, many people have investigated it because of its unique physical and chemical properties . Researchers have found that C 60 has a tremendous capacity to react with radicals to yield corresponding radical adducts.…”
Section: Introductionmentioning
confidence: 99%
“…FoF has been primarily attributed to poor physical performance, particularly mobility and balance impairments in older adults with DM (Bruce et al, 2015; Lalli et al, 2013; Munshi et al, 2012; Roman de Mettelinge et al, 2013). However, several other determinants for developing FoF overlap with the consequences/complications of DM, including but not limited to falls, muscle weakness, sensory impairments, depression, and cognitive decline (Deshpande, Metter, Lauretani, Bandinelli, & Ferrucci, 2009; Foote, Giuseffi, & Munshi, 2013; Scheffer, Schuurmans, Dijk, Hooft, & Rooij, 2008). Therefore, it is possible that the cumulative effect of these DM-related consequences may contribute to higher FoF severity and, consequently, greater activity restriction and deconditioning in older adults with DM.…”
mentioning
confidence: 99%